Розробка системи бронювання та продажу авіаквитків - Клочко, Є. С. (ХНУРЕ, 2024)
This project is dedicated to the development of a comprehensive system for booking and managing airline tickets. The system aims to streamline the process of ticket reservation and issue resolution for air travel. By integrating both server and client components, users will have access to a user-friendly interface for browsing available flights, selecting seats, and completing bookings. Additionally, the system will incorporate features for managing bookings, resolving issues, and providing assistance to travelers. Through this platform, airlines can efficiently manage their ticketing operations, while passengers can easily navigate and fulfill their travel requirements, ensuring a seamless and satisfying experience for all stakeholders involved in air travel.
Keywords: бронювання квитків; продаж авіаквитків; авіаквиток